On the enhancement of heat transfer in a backward-facing step using porous baffles - Cavaleiro Costa, Sérgio (2023)
The backward-facing step is a geometry often used not only to investigate the accuracy and performance of numerical models, but also to analyse fundamental flow and heat transfer characteristics, and the impact of different configurations for the most diverse problems primarily due to its similitude to tangible and more complex geometries. One of the fields of interest is its use for heat transfer problems, which is the focus of this work: using porous baffles to help increase heat transfer. The position and the dimensions of the baffle and operation conditions are varied and simulated using a 2-dimensional finite volume method. Flow is assumed to be steady, incompressible, and laminar. The optimal set of parameters is investigated using Genetic Algorithms. Due to the computational cost associated with the cost function, achieving results has been challenging, requiring the parallel computation of the cost function to shorten the computational time associated with each generation of the optimisation process. It is found that positioning the baffle in a way that deflects flow from the entry to the opposite and heated wall considerably increases heat transfer.